Elucidation of the Catalytic Pathway for the Direct Conversion of Furfuryl Alcohol into γ-Valerolactone over Al2O3–SiO2 Catalysts - Pichaya Chuangpusri; Sasiradee Jantasee; Patcharaporn Weerachawanasak; Weerachon Tolek; Chawalit Ngamcharussrivichai; Duangamol Nuntasri Tungasmita; Noppadon Sathitsuksanoh; Joongjai Panpranot (ACS Omega, 2023)
, and 15-120 min). The reaction pathways depend largely on the acid properties of the catalysts, especially the types of Bronsted (B) and Lewis (L) acid sites. A tandem alcoholysis/hydrogenation/cyclization sequence is dominant on the AlSi catalysts (Al ≥ 4%) and all the zeolites except MFI-1, resulting in complete conversion of FA and GVL with an yield 64-75% with IPL as the major side-product, regardless of the differences in their B/L ratios 0.06-1.35. In the absence of B acid sites (i.e., 0.2% AlSi and MFI-1 catalysts), FA could be straightforwardly converted into GVL on the weak Lewis acid sites from the isolated silanol groups using 2-propanol as a hydrogen source. The AlSi catalysts are promising tunable catalysts for FA conversion with good recyclability.
Keywords: Catalysis for Biomass Conversion; Mesoporous Materials and Catalysis; Supercapacitor Materials and Fabrication